Exploring trust in the boardroom: the case of Nordic region. Issue 3 (2nd June 2021) - Pastra, Aspasia; Koufopoulos, Dimitrios N.; Skintzi, Vasiliki; Johansson, Tafsir; Samac, Nikola
Abstract : Purpose: This paper aims to understand the relationship between the trust of executives in their board, board effectiveness (board performance and strategic decision quality) and organizational performance (financial and operational performance). Design/methodology/approach: Data were collected from 184 board members in the Nordic region, using cross-sectional research design. Confirmatory factor analysis was used to test the validity of the used scales, whereas correlational analysis and mediation analysis via PROCESS macro in SPSS were used for testing of the hypotheses. Findings: Trust between board members is positively correlated with both dimensions of board effectiveness and both tested dimensions of organizational performance. Besides, trust between the board members positively affects both financial and operational performance (significant total effects in mediation analysis). However, trust had a direct effect only on financial performance, whereas it shows an indirect effect on operational performance through both mediators, board performance and strategic decision quality. Research limitations/implications: Future research should investigate trust into the board using a longitudinal design, and expand the sample cross-culturally, and control for the influence of other interpersonal variables in board members. Practical implications: The development of trust in work relationships serves as the foundation for the establishment of significant team and organizational benefits. Business leaders should take into consideration trust issues in business teams and cultivate a trust culture in their organizations. Social implications: The findings advance theoretical, social and empirical understanding of trust of executives in their board and its effect on board performance, strategic decision quality and perceived performance. The development of trust in work relationships enhances team performance, networks with strategic partners, community and government, and serves as the foundation for the establishment of trust in the society. Originality/value: This is one of the scarce studies that examines direct and indirect effects of trust in board and organizational outcomes.